Effects Of Chrysin On The mRNA Expression Of Peroxisome Proliferator-Activated Receptor Alpha (PPARα) And Cyp Genes, Cell Cycle And Cell Migration In Colorectal Cancer Hct-116 Cells - Khor, Chin Yin (2020)
Peroxisome proliferator-activated receptor-alpha (PPARα) is reported to regulate the transcription of cytochrome P450 genes in human liver and intestine, which accounts for 70-80% of the enzymes involved in drug metabolism. Chrysin, on the other hand, is a natural phytochemical flavonoid that may possess a mild effect to be used as an anticancer agent. This study aimed to examine the effect of chrysin by investigating the mRNA expression level of PPARα and its related cellular mechanisms in treated HCT-116 cells, where camptothecin was used as a positive control The mRNA expressions of PPARα in HCT-116 cells treated with chrysin or a combination of chrysin and MK886 (PPARα inhibitor) were first determined using conventional PCR and then quantitatively analysed by Bioanalyzer.